EFEKTIVITAS COOLING TOWER FAN 6P - 4051 – GB. DI PT. PUPUK SRIWIDJAJA SEKTOR STG – BB, PALEMBANG, SUMATERA SELATAN - Triyansah, Olga; Witanto, Yovan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2020)
PT. Pupuk Sriwidjaja uses several cooling systems, one of which is the Cooling Tower Fan 6p - 4051 - GB cooling system. The cooling system is used for production machines especially in turbines. This practical work report will discuss the effectiveness of Cooling Tower Fan 6p - 4051-GB, by processing data on the temperature of incoming water, outlet water temperature, wet blub temperature and flow rate of water, then the calculation of actual data is then compared with ideal conditions, thus will be known how the performance of the Cooling Tower Fan 6p - 4051 - GB. From the analysis the ideal effectiveness value is 66.66% while for the actual effectiveness value is 64.5301%, the effectiveness decreases 2.136%. This is due to heat transfer from the system to the environment or vice versa. From the results of the analysis it can be seen in the data that the water temperature comes out at 10:00 always increases compared to the other hours. This is because at 10.00 the sunlight directly leads to the cooling tower water reservoir and on rainy days the effectiveness of the cooling tower will increase